Deleuze y el problema de la cultura (Zonas de fabulación local entre la Amazonía y la Patagonia). - Cangi, Adrián (Hermenéutica, 2024)
This paper considers the French philosopher's reservations about the institutional crystallization of "culture" and asks: What can we say about someone like Deleuze who detests the "seduction" produced by the word... as acts of "enunciation" or "expression" that escape, in the philosopher's judgment, from encounters with events that change meaning or with people who do things? To deal with culture, the question is a double and simultaneous task: to show what conditions its normative institution and to propose new conditions of experimentation. What matters is the liberating and warring force, as constructive as it is destructive, that can "unlearn" and "disbelieve" in order not to fall into the cells of culture. Our America exhibits inventive ways of using languages, syntax and rhetoric, pragmatics and stylistics, a key that is found in what the anthropologist Marcela Carneiro da Cunha or the linguist Luciana Storto called the "zone free of fabrication, speculation or imagination".